Indonesia Economic Quarterly : Private Investment is Essential - World Bank (World Bank, Washington, DC, 2016)
This Indonesia Economic Quarterly (IEQ) report discusses about the private investment which is essential for the economic growth of Indonesia. Indonesia needs to adjust to a global economy marked by slower growth, low commodity prices, and weaker trade and capital flows. In the short term, fiscal stimulus will help, but higher private investment is required for a firm recovery. Part C.1 of this edition further explores the issue of logistics sector reform. As Indonesia’s economy expanded rapidly since 2000, its freight logistics system has struggled to keep up. Indonesia’s transition to a more sustainable energy path can be supported by aligning pricing, regulations, and investment policies. The ultimate objective of the reform agenda is to reverse the recent trend of slower poverty reduction and rising inequality. Indonesians think reducing inequality is an urgent government priority. In addition to social protection programs and eradicating corruption, policies that create better work opportunities topped the list of policies respondents identified as important to address inequality.